Biomaterials and therapeutic applications. Issue 1 (January 2016) - Ferraro, Angelo
Abstract: A number of organic and inorganic, synthetic or natural derived materials have been classified as not harmful for the human body and are appropriate for medical applications. These materials are usually named biomaterials since they are suitable for introduction into living human tissues of prosthesis, as well as for drug delivery, diagnosis, therapies, tissue regeneration and many other clinical applications. Recently, nanomaterials and bioabsorbable polymers have greatly enlarged the fields of application of biomaterials attracting much more the attention of the biomedical community. In this review paper I am going to discuss the most recent advances in the use of magnetic nanoparticles and biodegradable materials as new biomedical tools.